2013
DOI: 10.1124/jpet.113.207878
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and Pharmacodynamic Properties of GS-9620, a Novel Toll-Like Receptor 7 Agonist, Demonstrate Interferon-Stimulated Gene Induction without Detectable Serum Interferon at Low Oral Doses

Abstract: GS -9620 [8-(3-(pyrrolidin-1-ylmethyl)benzyl)-4-amino-2-butoxy-7,8-dihydropteridin-6(5H)-one] is a potent, orally bioavailable small-molecule agonist of Toll-like receptor 7 (TLR7) developed for finite treatment of chronic hepatitis B viral (HBV) infection, with the goal of inducing a liver-targeted antiviral effect without inducing the adverse effects associated with current systemic interferon-a (IFN-a) therapies. We characterized the pharmacodynamic response of GS-9620 in CD-1 mice and cynomolgus monkeys fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 26 publications
4
73
0
Order By: Relevance
“…In this respect it is important to note that the recent demonstration of therapeutic efficacy in HBV-infected chimpanzees of a novel synthetic TLR agonist (GS-9620; labeled as a TLR7 agonist) was not only associated with serum detection of IFN-α, but also of increased IL-12 and CXCL10 levels [18]. Such a cytokine/chemokine profile is also consistent with a TLR8-mediated response and can be explained by the TLR7/TLR8 degeneracy of this synthetic compound at high doses [31].…”
Section: Discussionmentioning
confidence: 93%
“…In this respect it is important to note that the recent demonstration of therapeutic efficacy in HBV-infected chimpanzees of a novel synthetic TLR agonist (GS-9620; labeled as a TLR7 agonist) was not only associated with serum detection of IFN-α, but also of increased IL-12 and CXCL10 levels [18]. Such a cytokine/chemokine profile is also consistent with a TLR8-mediated response and can be explained by the TLR7/TLR8 degeneracy of this synthetic compound at high doses [31].…”
Section: Discussionmentioning
confidence: 93%
“…Specifically, formulated TLR7 agonist absorption and its effects are expected to be proportionally higher in the gut, because both agonist compounds have high absorption properties in the gastrointestinal (GI) tract and show only moderate clearance rates during the first phase of hepatic metabolism. Although these properties limit systemic exposure of TLR7 agonists after oral administration, they enhance drug exposure in the GI tract and the liver (18, 19, 24). Therefore, it is not surprising that the effects of these agonists appeared to be enhanced in the gut, as observed in the reduction of SIV DNA in CD4 + T cells from GMMCs.…”
Section: Discussionmentioning
confidence: 99%
“…This includes clinical trials evaluating the antiviral efficacy of IFN-l, that appears to have less side effects than IFN-a, as well as TLR7 agonists and therapeutic vaccines [53,54]. Furthermore, a recent study reported the potential of antibodies directed against the lymphotoxin-b receptor (LTbR) for HBV cure [55 ].…”
Section: Immunomodulatory Agentsmentioning
confidence: 99%